CHANGES IN THE IMMUNITY T-LINK OF HIGHLAND INHABITANTS DEPENDING ON THE DURATION OF LIVING IN LOWLAND (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2022)
The paper presents the results of comparison of T-lymphocytes parameters and their subpopulations. The results obtained reflect the changes in the indices of immunity T link of the population which live in highland depending on the terms of living in lowland.
Keywords: immune status, T-lymphocytes, helper T-lymphocytes, cytotoxic T-lymphocytes, immunoregulatory index, low mountains, high mountains, migration.